Cost-effectiveness analysis of PET/CT surveillance imaging to detect systemic recurrence in resected stage III melanoma: study protocol. Issue 11 (5th November 2020) - Dieng, Mbathio; Khanna, Nikita; Nguyen, Mai Thi Hoang; Turner, Robin; Lord, Sarah J; Menzies, Alexander M; Allen, Jay; Saw, Robyn; Nieweg, Omgo E; Thompson, John; Morton, Rachael L
Abstract : Introduction: In the new era of effective systemic therapies for advanced melanoma, early detection of lower volume recurrent disease using surveillance imaging can improve survival. However, intensive imaging follow-up strategies are likely to increase costs to health systems and may pose risks to patients. The objective of this study is to estimate from the Australian health system perspective the cost-effectiveness of four follow-up strategies in resected stage III melanoma over a 5-year period following surgical treatment with curative intent. Methods and analysis: A decision-analytic model will be built to estimate the costs and benefits of (1) 12 monthly, (2) 6 monthly, (3) 3–4 monthly positron emission tomography/CT imaging for 5 years, compared with (4) no imaging follow-up. The model will be populated with probabilities of disease recurrence, test performance measures using data from >1000 consecutive resected stage III melanoma patients from Melanoma Institute Australia diagnosed between 2000 and 2017. Healthcare resource use, including surveillance imaging, doctor's visits, subsequent tests and procedures to investigate suspicious findings, will be quantified from detailed patient records and valued using Australian reference pricing. Economic outcomes include cost per new distant melanoma recurrence detected and cost per diagnostic error avoided, for no imaging compared with the other strategies. Deterministic sensitivity analyses will examine the robustness of model results. Ethics and dissemination: This study was approved by the Sydney Local Health District, Sydney Local Health District Ethics Review Committee (RPAH Zone), AU/1/830638 and the Australian Institute of Health and Welfare (EO2019-1-454). The results of this study will be published in peer-reviewed medical and health economics journals and will inform melanoma management guidelines.